Estimation of height from the length of humerus in western region of Maharashtra - Borkar, Meenakshi P. (International Journal of Research in Medical Sciences, 2017)
An attempt has been made to find out correlation and to drive a regression formula between the length of humerus and height of an individual, in western region of Maharashtra. The material consisted of 200 undergraduate and post-graduate medical students of age group 20 to 30 years from western region of Maharashtra. The length of humerus is measured by asking the subject to flex the elbow joint. The flexor surfaces of arm and forearm made an angle of 90 degree. The lateral epicondyle was felt and marked with skin marking pencil. Acromion point was traced by moving finger over clavicle’s lateral end and was marked. The distance between two points was measured by spreading caliper, both side humerus length was taken. The measured length was subtracted by 2.0 mm as the acromion point is 2 to 5 mm above humeral head. Height of the subject was measured with standard height measuring instrument in anatomical position. The results obtained were analyzed and attempt was made to derive a formula between length of humerus and total height of an individual. The result shows that there is definite correlation between the two.